Case Study of Illegal Online Fintech Lending (Fintech Lending) in Indonesia in Strategic Intelligence Perspective - Herlambang, Yuriandi; Rofii, Muhammad Sya'roni (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
Besides having a positive impact on the economy, the rapid development of the financial technology (fintech) industry, which still has weak supervision and low public understanding, has led certain parties to make fintech a crime medium, such as the rise of online loans that do not comply with regulations. Using a qualitative approach with a case study method, this paper analyzes data from related agency documents, to explain the phenomenon of fintech lending or known as online lending (pinjol) in Indonesia from the point of view of strategic intelligence. From the data and analysis carried out, it was found that borrowing is not only detrimental to the economy but also has an impact on the social aspects of the community. The ease of making loan applications, unclear regulations coupled with low public understanding, and high economic needs have made illegal lending grow rapidly.